2001
DOI: 10.1016/s0896-6273(01)00291-4
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin Regulates Target Specificity in the Drosophila Visual System

Abstract: Using visual behavioral screens in Drosophila, we identified multiple alleles of N-cadherin. Removal of N-cadherin selectively from photoreceptor neurons (R cells) causes deficits in specific visual behaviors that correlate with disruptions in R cell connectivity. These defects include disruptions in the pattern of neuronal connections made by all three classes of R cells (R1-R6, R7, and R8). N-cadherin is expressed in both R cell axons and their targets. By inducing mitotic recombination in a subclass of eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
250
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(267 citation statements)
references
References 47 publications
17
250
0
Order By: Relevance
“…R7 terminals show extensive contacts with each other before segregation into separate columns. Given the expression of a number of cell adhesion molecules such as N-Cadherin and Chaoptin on R7 terminals throughout development (Van Vactor et al, 1988;Lee et al, 2001), it seems clear that a repulsive force or an anti-adhesion mechanism is necessary to overcome the adhesion and thus facilitate the segregation of adjacent R7 terminals. Mutual repulsion has been suggested to be required for columnar restriction of L1 neurons in the Drosophila visual system, which is mediated by Dscam2 (Millard et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…R7 terminals show extensive contacts with each other before segregation into separate columns. Given the expression of a number of cell adhesion molecules such as N-Cadherin and Chaoptin on R7 terminals throughout development (Van Vactor et al, 1988;Lee et al, 2001), it seems clear that a repulsive force or an anti-adhesion mechanism is necessary to overcome the adhesion and thus facilitate the segregation of adjacent R7 terminals. Mutual repulsion has been suggested to be required for columnar restriction of L1 neurons in the Drosophila visual system, which is mediated by Dscam2 (Millard et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…PM181-Gal4 (ref. 8) is expressed in R7 photoreceptors, and mδ-GAL4 (generated by P. Garrity; Massachusetts Institute of Technology) is expressed in R3/R4 photoreceptors. Both lines were independently combined with the reporter line UAS-mCD8-GFP 24 and used both to examine photoreceptor neurons in the third larval stage and as a marker for cell sorting.…”
Section: Methodsmentioning
confidence: 99%
“…The mδ promoter drives expression in R3/R4 photoreceptors that project to the lamina region 7 (Fig. 2b,c), and the PM181 promoter labels R7 photoreceptors that project to the medulla 8 (Fig. 2d,e).…”
Section: Dscam Expression In Different Cell Typesmentioning
confidence: 99%
“…In Drosophila N-cad is essential for target specificity of visual axons in the compound eye (Lee et al, 2001). Recently, Lele et al (2002) analyzed zebrafish parachute/n-cadherin mutants and demonstrated that N-cad is required for morphogenesis and maintained integrity of the neural tube.…”
Section: Introductionmentioning
confidence: 99%